PENDAMPINGAN PEMANFAATAN GENERATIVE ARTIFICIAL INTELLIGENCE (GenAI) UNTUK MENINGKATKAN KAPASITAS PEMASARAN DIGITAL PELAKU USAHA TOKO KELONTONG DI KOTA PROBOLINGGO - Fitri Dian Wilujeng (LPPM STAI Muhammadiyah Probolinggo, 2026)
The micro, small, and medium enterprise (MSME) sector, particularly local traditional grocery stores, holds a vital position in supporting regional economies. However, this business group often faces major barriers when adopting modern marketing technologies due to limited digital literacy and minimal operational capital. This collaborative community service program was initiated to escalate the digital marketing capacity of 15 grocery store operators in the Probolinggo City area through a mentoring scheme based on Generative Artificial Intelligence (GenAI) implementation. The program's execution adopted the Participatory Action Research (PAR) framework, implemented through three strategic stages: basic education on digital marketing and GenAI ecosystems, intensive guidance in producing AI-assisted promotional content, and continuous ongoing monitoring of implementation outcomes. Program success is reflected in the significant surge of participants' theoretical understanding of digital marketing from an initial average of 35% to 85%, technical skills in creating promotional materials from 20% to 90%, and a 60% time efficiency in content composition. All partner entrepreneurs (100%) successfully activated business-specific social media accounts and productively generated advertisements using GenAI. This activity confirms that structured mentoring optimizing GenAI serves as a highly applicable solution to boost the digital marketing capabilities of traditional micro-retail MSMEs with limited technological literacy